Good Corporate Governance Sebagai Prinsip Dasar Pengelolaan Badan Usaha Milik Daerah oleh Pemerintah Daerah di Sumatera Barat - Shalsa Anugerah Deri Putri; Febby Mutiara Nelson (Jurnal Pembangunan Nagari, 2023)
Regional Owned Enterprises (BUMD) are one of the tangible forms of separated regional wealth management results. BUMD regulation is contained in the Law of the Republic of Indonesia Article Number 23 of 2014 which is one of the realizations from the principle of regional autonomy that states an autonomous region can plan their regional economic development based on their resources. BUMD aims for the regions to take the advantages of this business entity as a support for their regional income. This study aims to find out that the principles of good corporate governance are the foundation of BUMD management. The method that is used in this research is juridical-normative by using a statutory approach. The legal materials used are primary, secondary, and tertiary legal materials by using descriptive-analytical analysis techniques. From the results of the study, the conclusion is local government has a very important role to realize governance good management in BUMD. Besides that, it was found that the principle of good corporate governance is a basic principle so it must exist in the management of BUMD.